Effect Of Cryogenic Treatment Prior To Equal Channel Angular Press (ECAP) Of Sac Solder - Koay, Tze Yen (Universiti Sains Malaysia, 2018)
The SAC solder alloy has been proposed as the alternative solder to overcome the environmental concern of lead (Pb-Sn) solder. Many researchers have studied the SAC solder alloy and found that reliability issues of solder on mechanical properties such as hardness and strength. The present work aims to look at how grain refinement influenced the mechanical properties of a commercial SAC 305 solder alloy. In this work, SAC 305 solder were subjected to severe plastic deformation applied via Equal Channel Angular Pressing (ECAP) which was conducted through route BC. Prior to ECAP, the solder alloy was dipped in liquid nitrogen for cryogenic treatment. It is believed that cryogenic treatment (CT) can improve the microstructure and performance of solder. The effect of the dipping time of samples in liquid nitrogen and number of passes through ECAP employed during pressing on hardness was studied. Elemental analysis of casted solder alloy was analysed using XRF and it showed correct composition of SAC 305. Phases and crystallite size of all the solders were examined by XRD and sample with cryogenic treatment prior to ECAP exhibited a smaller crystallite size. Solder alloy with dipping in liquid nitrogen prior to ECAP enhanced the Vickers microhardness of bulk solder alloy. This is due to the microstructure of solder alloys with dipping of liquid nitrogen prior to ECAP showed evidence of grain refinement as observed using Scanning electron microscope (SEM). Besides, CT prior to ECAP improved the spreading and wetting angleof reflowed solder on Cu substarate. For the mechanical properties, solder joint samples with dipping in liquid nitrogen for shortest time of 10 minutes prior to ECAP gave the highest shear strength through single lap joint test and the fracture surface showed smaller dimples compared to others. In conclusion, grain refinement and mechanical properties of solder alloy improved through CT prior to ECAP.